การพัฒนาหลักสูตรฝึกอบรมเพื่อเสริมสร้างทักษะชีวิตสำหรับนักเรียนพยาบาลทหารอากาศ A Development of Training Program to Enhance Life Skills for The Royal Thai Air Force Nursing Students - ไทรแจ่มจันทร์ สกาวเนตร; สกุลคู จารุวรรณ; โพธิสุข อรรณพ; ยงศร จตุพล (Journal of The Royal Thai Army Nurses, 2015)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาองค์ประกอบทักษะชีวิตของนักเรียนพยาบาล สังกัดกระทรวงกลาโหม 2) เพื่อพัฒนาหลักสูตรฝึกอบรมเพื่อเสริมสร้างทักษะชีวิตสำหรับนักเรียนพยาบาลทหารอากาศ และ 3) เพื่อศึกษาประสิทธิภาพของหลักสูตรฝึกอบรมเพื่อเสริมสร้างทักษะชีวิตสำหรับนักเรียนพยาบาลทหารอากาศ กลุ่มตัวอย่างที่ใช้ในการวิจัยแบ่งเป็น 2 กลุ่ม คือ 1) กลุ่มตัวอย่างที่ใช้ในการศึกษาองค์ประกอบทักษะชีวิตของนักเรียนพยาบาล สังกัดกระทรวงกลาโหม ปีการศึกษา 2556 ได้มา จากการสุ่มอย่างง่าย จำนวน 516 คน และ 2) กลุ่มตัวอย่างที่ผู้วิจัยใช้ในการศึกษาประสิทธิภาพของหลักสูตรฝึกอบรมเพื่อเสริมสร้างทักษะชีวิตสำหรับนักเรียนพยาบาลทหารอากาศ เป็นนักเรียนพยาบาลทหารอากาศ ชั้นปีที่ 1 ปีการศึกษา 2556 จำนวน 45 คน เครื่องมือที่ใช้ในการวิจัยเป็นแบบสอบถามทักษะชีวิต หลักสูตรฝึกอบรม แบบสอบถามความพึงพอใจต่อหลักสูตรฝึกอบรม วิเคราะห์ ข้อมูลโดยหาค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน การทดสอบที และการวิเคราะห์องค์ประกอบเชิงยืนยัน ผลการศึกษาค้นพบองค์ประกอบทักษะชีวิตของนักเรียนพยาบาล สังกัดกระทรวงกลาโหม ว่าประกอบด้วย 5 องค์ประกอบ ได้แก่ การตระหนักรู้ในตนเอง การแก้ปัญหา การจัดการอารมณ์ การเห็นอกเห็นใจผู้อื่น และการสร้างสัมพันธภาพระหว่างบุคคล มีค่าความเหมาะสมพอดีกับข้อมูลเชิงประจักษ์ มีน้ำหนักองค์ประกอบมาตรฐานอยู่ในเกณฑ์สูง อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 และสามารถวัดองค์ประกอบของทักษะชีวิตของนักเรียนพยาบาลได้ สำหรับหลักสูตรฝึกอบรมเพื่อเสริมสร้างทักษะชีวิตสำหรับนักเรียน พยาบาลทหารอากาศ ประกอบด้วย 4 ด้าน ได้แก่ 1) วัตถุประสงค์ของหลักสูตรฝึกอบรม 2) โครงสร้างเนื้อหาสาระของหลักสูตร ฝึกอบรม 3) วิธีดำเนินการฝึกอบรม และ 4) การวัดและประเมินผลการฝึกอบรม หลักสูตรฝึกอบรมเพื่อเสริมสร้างทักษะชีวิตสำหรับนักเรียนพยาบาลทหารอากาศที่ผู้วิจัยสร้างขึ้นมีคุณภาพดี และมีความเหมาะสมสามารถนำไปใช้ในการฝึกอบรม เพื่อเสริมสร้างทักษะชีวิตได้ โดยพิจารณาจากผลค่าคะแนนความ พึงพอใจต่อหลักสูตรฝึกอบรม เพื่อเสริมสร้างทักษะชีวิตสำหรับนักเรียนพยาบาลทหารอากาศ พบว่า ผู้เข้ารับการฝึกอบรมมีความพึงพอใจต่อหลักสูตรฝึกอบรมโดยภาพรวมอยู่ในระดับมาก ค่าเฉลี่ย 4.31 ค่าเบี่ยงเบนมาตรฐาน 0.66 The purposes of this study were to 1) study life skill components of nursing student under Ministry of Defense, 2) to develop a training program to enhance life skills for the Royal Thai Air Force nursing students, and 3) to validate the efficacy of the training program. The subjects were students of Nursing Colleges under the Ministry of Defense. The first group of 516 was randomly selected to participate in a life skills component study and the second group of 45 to participate in the program validation process. The instruments used for collecting data were life skills questionnaires, the training program and appropriateness of the training program questionnaires. The statistical method used for analyzing data included percentage, mean, standard deviation, t-test (dependent) and confirmatory factor analysis. The results were as follow: The confirmatory factor analysis significantly confirmed that the model of the life skills function could be characterized into five factors: self-awareness skills component, problem solving skills component, emotion management skills component, empathy skills component and interpersonal relationship skills component. These five factors had high loading at the .05 significant level and could be used to measure the life skills of nursing students. The life skills training program consisted of four aspects, rationale of the curriculum, purpose of the curriculum, conceptual framework of the curriculum, implementation technique, and measurement and evaluation methodology. The life skills training program for nursing students developed was highly appropriate to be implement to enhance nursing students life skills. Statistically significant differences in the total life skills and in each life skills component of the experimental group existed before and after participating in the training program at the .05 level. The results of this study indicated that the life skills training program was a key factor in increasing change in the life skills of the nursing students. The experimental group also rated the appropriateness of the training program at a high level.